Numerical Investigation of the Effect of Biodiesel-Biogas Percentage on Performance Characters and Dual Fuel Engine Emissions as Green Technology on Ship - Betty Ariani; Dedy Wahyudi (Department of Naval Architecture - Diponegoro University, 2022)
The discourse on the application of green technology in the maritime sector is an interesting agenda to implement. The development of the world of shipping transportation which continues to experience an increase in numbers and services creates new problems in terms of fuel supply and the resulting emissions. So that the development of innovation and technology for ship machinery should be directly related to fossil fuel substitution technology, operational efficiency technology, improving performance and reducing emissions from the engine itself to be achievements and targets. Good engine performance directly has an impact on increasing the operational efficiency of the ship and being a good carrying capacity in the environment with minimal emission levels. A dual-fuel engine is one of the engine system concepts that has several advantages, such as simple and relatively easy modifications and the use of natural gas which tends to be cleaner. Biodiesel and biogas are examples of alternative fuels that are expected to be promising solutions for marine engineering. This research uses a numerical study on the application of dual fuel engines, the percentage of biodiesel-biogas is carried out with variations of 50:50 and 25:75, at a constant engine speed of 2200 RPM. Simulations were carried out to see the results of how the engine performance, cylinder pressure, heat release rate and HC and NOx emissions were at a constant speed variation of the fuel percentage test NOx emission decreased at a higher biogas percentage, for UHC it increased at a higher biogas percentage, it is possible to add oxygen intake through a turbocharger or supercharger as an auxiliary equipment.